Forgery of Sale and Purchase Deed (AJB) by Land Deed Official (PPAT) in the Land Dispute Case of Nirina Zubir - Izza Safira; Riana Susmayanti; Ahmad Najmi Faris (Socio-Economic and Humanistic Aspects for Township and Industry, 2024)
An Authentic Deed is a document that holds perfect evidentiary power regarding the statements contained within it, without the need for additional evidence. This is because authentic deeds are created based on the provisions of laws and regulations. In 2021, a land mafia case emerged involving the Notary/Land Deed Official (PPAT) profession. The case began when the household assistant (ART) of Nirina Zubir's family offered to help Nirina Zubir's mother recover six lost land ownership certificates by involving a Notary/PPAT she knew. This research employs a juridical-normative method with a statutory and case approach. Normative legal research examines legal literature, secondary data, and tertiary legal materials. In this case, it is indicated that there is a legal flaw in the process of transferring land rights without the direct consent of the concerned parties. In the performance of duties by the Notary/PPAT, particularly regarding the issuance of powers to sell land rights, it is crucial that regulations governing Notaries/PPAT are strictly adhered to. The sale and purchase deed was made without fulfilling several necessary aspects that determine its validity. A legal review was conducted on the PPAT notary, who is authorized to issue the deed of sale and purchase, which was later used as a document in applying for a replacement certificate of ownership (SHM) at the National Land Agency (BPN).